Selected topics in electronics and systems - nanotechnology for electronics, photonics, biosensors, and emerging technologies - Jain, F; Broadbridge, Christine; Gherasimova, M; Tang, H (WORLD SCIENTIFIC, 2020)
Keywords: dept.phy

Selected topics in electronics and systems - nanotechnology for electronics, biosensors, additive manufacturing and emerging systems applications - Jain, F; Broadbridge, Christine; Gherasimova, M; Tang, H (WORLD SCIENTIFIC, 2021)
Keywords: dept.phy

Road salt compromises functional morphology of larval gills in populations of an amphibian. - Szeligowski, Richard V.; Scanley, Jules A.; Broadbridge, Christine C.; Brady, Steven P. (Environmental pollution (Barking, Essex : 1987), 2021)
Across the planet, winter de-icing practices have caused secondary salinization of freshwater habitats. Many amphibians are vulnerable because of permeable skin and reliance on small ponds, where salinity can be high. Early developmental stages of amphibians are especially sensitive to salt, and larvae developing in salt-polluted environments must osmoregulate through ion exchange in gills. Though ionoregulation in amphibian gills is generally understood, the role of gill morphology remains poorly described. Yet gill structure should affect ionoregulatory capacity, for instance in terms of available surface area. As larval amphibian gills also play critical roles in gas exchange and foraging, changes in gill morphology from salt pollution potentially affect not only osmoregulation, but also respiration and feeding. Here, we used an exposure experiment to quantify salinity effects on larval gill morphology in wood frogs (Rana sylvatica). We measured a suite of morphological traits on gill tufts—where ionoregulation and gas exchange occur—and on gill filters used in feeding. Larvae raised in elevated salinity developed larger gill tufts but with lower surface area to volume ratio. Epithelial cells on these tufts were less circular but occurred at higher densities. Gill filters showed increased spacing, likely reducing feeding efficiency. Many morphological gill traits responded quadratically, suggesting that salinity might induce plasticity in gills at intermediate concentrations until energetic demands exceed plasticity. Together, these changes likely diminish ionoregulatory and respiratory functionality of gill tufts, and compromise feeding functionality of gill filters. Thus, a singular change in aquatic environment from a widespread pollutant appears to generate a suite of consequences via changes in gill morphology. Critically, these changes in traits likely compound the severity of fitness impacts in populations dwelling in salinized environments, whereby ionoregulatory energetic demands should increase respiratory and foraging demands, but in individuals who possess structures poorly adapted for these functions. © 2021 Elsevier Ltd
2 citations (Crossref) [2023-10-31]
Keywords: Amphibia; Animals; Article; Feeding; Freshwater habitats; Functional morphology; Gas exchange; Gill morphology; Gills; Humans; Ion exchange; Larva; Morphology; Osmoregulation; Osmosis; Osmotic stress; Plasticity; Pollution; Rana sylvatica; Ranidae; Road effect; Road salts; Roads and streets; Salinisation; Secondary salinization; Sodium Chloride; Surface area; amphibian; animal; animal cell; animal experiment; animal tissue; aquatic environment; breathing; cell density; cell structure; controlled study; dept.bio; developmental stage; embryo; energetic demand; energy; epithelium cell; exposure; foraging; functional morphology; gill; gill filter; gill length; gill tuft; human; larva; length; nonhuman; osmoregulation; peer-reviewed; plasticity; pollution exposure; road; salinity; salinization; salt; sodium chloride; surface area; volume

Waste Citrus reticulata Assisted Preparation of Cobalt Oxide Nanoparticles for Supercapacitors - Srivastava, Rishabh; Bhardwaj, Shiva; Kumar, Anuj; Singhal, Rahul; Scanley, Jules; Broadbridge, Christine C.; Gupta, Ram K. (Nanomaterials, 2022)
The green, sustainable, and inexpensive creation of novel materials, primarily nanoparticles, with effective energy-storing properties, is key to addressing both the rising demand for energy storage and the mounting environmental concerns throughout the world. Here, an orange peel extract is used to make cobalt oxide nanoparticles from cobalt nitrate hexahydrate. The orange peel extract has Citrus reticulata, which is a key biological component that acts as a ligand and a reducing agent during the formation of nanoparticles. Additionally, the same nanoparticles were also obtained from various precursors for phase and electrochemical behavior comparisons. The prepared Co-nanoparticles were also sulfurized and phosphorized to enhance the electrochemical properties. The synthesized samples were characterized using scanning electron microscopic and X-ray diffraction techniques. The cobalt oxide nanoparticle showed a specific capacitance of 90 F/g at 1 A/g, whereas the cobalt sulfide and phosphide samples delivered an improved specific capacitance of 98 F/g and 185 F/g at 1 A/g. The phosphide-based nanoparticles offer more than 85% capacitance retention after 5000 cycles. This study offers a green strategy to prepare nanostructured materials for energy applications.
3 citations (Crossref) [2023-10-31] Number: 23
Keywords: Citrus reticulata; Co_3O_4 nanoparticles; characterization; charge storage; dept.phy; peer-reviewed; supercapacitors

Effect of multi-wall carbon nanotubes on electrochemical performances of MnO2 - Singhal, Rahul; Saini, Bhagirath; Kiehnle-Benitez, Monica; Sadowski, Thomas; Broadbridge, Christine; Scanley, Jules; LeMaire, Peter K.; Sharma, Rakesh K. (AIP Advances, 2022)
Composites of MnO2/multi-wall carbon nanotubes (MWCNTs) were prepared using different weight ratios of MWCNTs: KMnO4 (1:2, 1:5, 1:10, 1:15, 1:20, and 1:25) using a one-pot hydrothermal method. The synthesized materials were physically characterized by x-ray diffraction, transmission electron microscopy (TEM), field emission-scanning electron microscopy (FE-SEM), (Brunauer–Emmett–Teller) BET, and thermogravimetric analysis. TEM and SEM studies indicate that MnO2 is homogeneously entangled with MWCNTs. The electrochemical performance evaluation was performed in a 3-electrode system using MnO2/MWCNT electrodes coated onto a Ni mesh as the working electrode, a Pt foil as the counter electrode, and Ag/AgCl as the reference electrode. The specific capacitance was obtained from charge–discharge studies at varying current densities between 0.5 and 5 A/g. The specific capacitance of MWCNT-KMnO4 (1:10, 1:15, and 1:25) samples was obtained as 114, 164, and 100 F/g, respectively, at a current density of 1 A/g.
2 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Synthesis and characterization of CuS, CuS/graphene oxide nanocomposite for supercapacitor applications - Singhal, Rahul; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Sharma, Rakesh K. (AIP Advances, 2020)
Supercapacitors or electrochemical capacitors are receiving greater interest because of their high-power density, long life, and low maintenance. We have synthesized CuS nanoparticles and graphene oxide (CuS-GO) nanocomposites for supercapacitor applications because of their low cost and excellent electrochemical properties. The phase purity of each material was determined using powder XRD studies. The bandgap was determined by UV-visible spectrophotometric studies. Scanning electron microscope and transmission electron microscope images revealed the nano-scale morphology of the synthesized particles. All the electrochemical measurements were conducted in a standard three-electrode configuration, using a platinum wire as the counter electrode and Hg/HgO as the reference electrode. CuS and its composites with graphene oxide on nickel foam were used as working electrodes. All the electrochemical measurements were performed in 3M KOH solution. The CuS-GO nanocomposite electrode showed a specific capacitance of 250 F/g, 225 F/g, 182 F/g, 166 F/g, 161 F/g, and 158 F/g at a current density of 0.5 A/g, 1 A/g, 5 A/g, 10 A/g, 15 A/g, and 20 A/g, respectively. CuS-GO electrodes showed a specific capacitance retention of 70% after 5000 charge-discharge cycles at a current density of 5 A/g. © 2020 Author(s).
19 citations (Crossref) [2023-10-31] WOS:000519123100001
Keywords: Capacitance; Charge-discharge cycle; Copper compounds; Electric discharges; Electrochemical capacitor; Electrochemical electrodes; Electrochemical measurements; Foams; Graphene; Mercury compounds; Nanocomposite electrodes; Nanocomposites; Potassium hydroxide; Scanning electron microscopy; Spectrophotometric study; Supercapacitor; Supercapacitor application; Synthesis (chemical); Synthesis and characterizations; Transmission electron; Transmission electron microscopy; dept.phy; peer-reviewed

Effect of reduce graphene oxide (Rgo) on electrochemical performance of Cus for supercapacitor applications - Singhal, Rahul; Thorne, David; Chaudhary, Manika; Bhardwaj, Shiva; Abazi, Rilind; Gupta, Ram K.; Scanley, Jules; Broadbridge, Christine C.; Singh, B. P.; LeMaire, Peter K.; Sharma, Rakesh K. (2023)
CuS and CuS-rGO nanocomposites were synthesized by the hydrothermal method. The synthesized CuS and rGO-CuS nanocomposite materials were physically characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) and were evaluated electrochemically for supercapacitor applications. The specific capacitance of CuS was determined to be 207 F/g, 150 F/g, and 97 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350 F/g, 251 F/g, and 149 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively.
Keywords: CuS; SEM; Supercapacitors; dept.phy; rGO; specific capacitance